The Integrasi OEE dan Six Big Losses Untuk Meningkatkan Nilai Efektivitas Mesin Steamer (Pendekatan FMEA di UMKM Marrone Brownies) - Renno Angga Mardian; Elly Wuryaningtyas Yunitasari; Emmy Nurhayati (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2022)
The problem that often occurs in production target are not achieved is breakdown engine. Machines are the core of production. As is the case UMKM Marrone is a home industry for making brownies that uses machines as foundation of its production. One of the machines used is steamer ks-601. Steamer machine is a machine used to steam a brownies. The damage that occurs to the steamer engine is due to lack of maintenance, causing the steamer engine performance to not be optimal. The methods used to reduce engine damage are Overall Equipment Effectiveness, six big losses, and Failure Mode and Effect Analysis. OEE aims to improve the performance of a device. Six big losses are six losses caused by the use of ineffective equipment. FMEA is a factor that affects failure with the aim of obtaining factors that require further treatment. The results of the application of OEE found that the average calculation of the OEE of the steamer was 82.19%, still below the JIPM standard, which was 85. Then based on the six big losses, the breakdown losses were 6.08%, set up & adjustment losses were 5.21%, idling minor & stoppage losses were 21.42%, reduced speed losses were 1.48%, process defect losses were 5.04%, and reduced yield 0%. Analysis using the FMEA method shows that the highest RPN is at the turn of the fire adjust switch 175. Then the proposed improvement is carried out using the automatic maintenance method with the CILT stage.